The Inversion at Compose with a Separator Do and a Rhythmic Do in English Declarative Sentences - Mirzaaliyev Ikromjon Mirzakarimovich; Shokirova Markhabo Sharifovna (Researchparks Publishing, 2021)
We use inversion in several different situations in English. Inversion just means putting the verb before the subject. We usually do it in question forms. The article discusses the inversion at compose with a separator do and a rhythmic do in English sentences.